ARTIFICIAL INTELEGENCE TECHNOLOGY IS SHAPING THE WOUND CARE - Ronald Winardi Kartika; Soegianto Ali (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2022)
Chronic wounds cause significant morbidity and mortality in the health care system.1 Patients with chronic wounds require frequent visits for evaluation by health professionals. The main indicator of healing is wound reduction surface area that helps doctors determine the progress of healing and choose the right therapy. conventional wound care using photo planimetry is the safest and most effective way to provide wound care and to ensure continuous monitoring; this. Telemedicine approaches that involve remote monitoring are more suitable from both an economic and patient experience point of view. However, prompt intervention is proving difficult, and healthcare professionals must be able to ensure a high standard of care. Several technological support tools for wound care professionals that have provided ulcer morphology measurements are able to provide automatic diagnostic information through a standard wound classification scale using the Artificial Intelligence (AI) method.